Generation of internal solitary waves by frontally forced intrusions in geophysical flows - Daniel Bourgault (Nature Portfolio, 2016)
Internal solitary waves are widespread within oceans, lakes and the atmosphere but their origin is uncertain. Here we show a rare natural case of the birth of internal solitary waves arising from the head of a frontally-forced intrusion as observed in the Saguenay Fjord, Canada.